Shining light on the histamine H2 receptor: Synthesis of carbamoylguanidine-type agonists as a pharmacological tool to study internalization. (15th November 2021) - Tropmann, Katharina; Seibel-Ehlert, Ulla; Littmann, Timo; Strasser, Andrea
Graphical abstract: Abstract: So far, only little is known about the internalization process of the histamine H2 receptor (H2 R). One promising approach to study such dynamic processes is the use of agonistic fluorescent ligands. Therefore, a series of carbamoylguanidine-type H2 R agonists containing various fluorophores, heterocycles, and linkers (28 –40 ) was synthesized. The ligands were pharmacologically characterized in several binding and functional assays. These studies revealed a significantly biased efficacy (Emax ) for some of the compounds, e.g. 32 : whereas 32 acted as strong partial (Emax : 0.77, mini-Gs recruitment) or full agonist (Emax : 1.04, [ 35 S]GTPγS binding) with respect to G protein activation, it was only a weak partial agonist regarding β-arrestin1/2 recruitment (Emax : 0.09–0.12) and failed to promote H2 R internalization (confocal microscopy). On the other hand, H2 R internalization was observed for compounds that exhibited moderate agonistic activity in the β-arrestin1/2 pathways (Emax  ≥ 0.22). The presented differently-biased fluorescent ligands are versatile molecular tools for future H2 R studies on receptor trafficking and internalization e.g. using fluorescence microscopy.